The influence of brain gym on changes in the numerical ability of grade I elementary students - Atika Agustina; Rayi Ardhiani (Physical Therapy Journal of Indonesia, 2023)
Introduction: The child is one of the important human resources in building a nation with improved quality and quality of life. One of which is the issue of education. Education is a process of self-development potential to increase optimal knowledge. Therefore, using a brain gym to improve children's learning abilities is more optimal. This study is to determine the effect of brain gym on the change of numeracy skills in grade 1 elementary school children. Methods: This research was pre-experimental with a one-group pretest-posttest approach with purposive sampling. The respondents were 19 samples that fulfilled the inclusion and exclusion criteria in public elementary school 1 Jatiwarna, Bekasi, Indonesia. Data were taken before and after the three weeks of brain training exercises using the 1st-grade end-of-year skills test. Analysis of univariate data used Shapiro Wilk and bivariate using paired sample t-test. Results: From 20 respondents, the average counting ability before intervention was 65.20, and after intervention was 80.60. The results showed an effect of the Brain Gym intervention on the counting abilities of children with p=0.000 <α (0.05). Conclusion: Based on these results, it can be concluded that exercise brain gym influenced the increase in children's numeracy skills at Public Elementary School 1 Jatiwarna Bekasi in 2018.